Tafsir Alquran Kontemporer: Kajian atas Tafsir Tematik-Kontekstual Ziauddin Sardar - Anggoro, Taufan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
Ziauddin Sardar is a Muslim thinker who interprets the Koran in a thematic-contextual, with a very critical presentation. Sardar’s interpretation is contained in one of his works entitled Reading the Qur’an: The Contemporary Relevance of the Sacred Text of Islam. This article aims to examine the thoughts of Sardar in terms of interpreting the Qur’an. The extent to which the methodology used by Sardar in interpreting the Qur’an. By using descriptive-analytical methods and hermeneutical-analysis techniques, Sardar’s interpretation is examined to what extent hermeneutic operational forms appear within them. It also examined how the influences of other figures in ‘shaping’ Sardar’s interpretation. The results of this study show that Sardar’s contextual interpretation reveals forms of hermeneutic surgery. Where more ‘aiming’ aspects of the context and contextualization of the Qur’an. Then methodologically, Sardar’s interpretation was influenced by Rahman’s double movement theory, and Saeed’s legal ethico theory. Then the style of “Hermeneutics of Liberation” Farid Esack was strongly felt in the contextualization of the Koran by Sardar. Sardar’s efforts are not limited to explaining the meaning of the Qur’an, but digging into the substance of the text that is manifested in the form of al-Qur’an’s social criticism of various religious phenomena today.